2011
DOI: 10.1109/tmtt.2010.2090169
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Neuro-Space Mapping Technique for Modeling of Nonlinear Microwave Devices

Abstract: Abstract-This paper presents a new advance in Neuro-space mapping (Neuro-SM) techniques for modeling nonlinear microwave devices. Suppose that existing device models (namely, coarse models) cannot match the behavior of a new device (referred to as the fine model). By neural network mapping of the voltage and current signals from the coarse to the fine models, Neuro-SM can modify the behavior of the coarse model to match that of the fine model. However, the efficiency of mapping depends on both the mapping stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 37 publications
0
50
0
Order By: Relevance
“…Our proposed neuro‐SM is a further advance over the previous techniques in other works , , , . Compared with the work of Zhang et al where only voltage mappings were considered, our proposed technique considers separate mappings for voltage and current.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Our proposed neuro‐SM is a further advance over the previous techniques in other works , , , . Compared with the work of Zhang et al where only voltage mappings were considered, our proposed technique considers separate mappings for voltage and current.…”
Section: Discussionmentioning
confidence: 84%
“…Moreover, obvious accuracy improvement using the proposed neuro‐SM over the traditional neuro‐SM presented by Zhang et al can be observed. The proposed neuro‐SM model is more accurate than the resulting model built by the DC and small‐signal training methods of Gorissen et al and Zhu et al owing to the inclusion of large‐signal HB data for both voltage and current mapping neural network training.…”
Section: Proposed Neuro‐sm Modeling Examplesmentioning
confidence: 91%
See 2 more Smart Citations
“…This technique uses neural networks to map the voltage or current signals of the existing device model into that of the device data. The Neuro-SM method can be applied to not only the simple DC and S-parameters modeling of nonlinear devices, but also the complex large-signal modeling [6,7,8]. In [9], a dynamic neural network is used as the mapping network for the Neuro-SM model of power transistors.…”
Section: Introductionmentioning
confidence: 99%